Walter Benjamin and the Antinomies of Tradition - McCole, John (Book collections on Project MUSE., 2018)
Few modern thinkers have been as convinced of the necessity of recovering the past in order to redeem the present as Walter Benjamin (1892-1940). Benjamin at once mourned and celebrated what he took to be an inevitable liquidation of traditional culture, and his determination to think both of these attitudes through to their conclusions lends his work its peculiar honesty, along with its paradoxical, antinomial coherence. In a landmark interpretation of the whole of Benjamin's career, John McCole demonstrates a way of understanding Benjamin that both contextualizes and addresses the complexities and ambiguities of his texts.Working with Pierre Bourdieu's concept of the "intellectual field," McCole traces Benjamin's deep ambivalence about cultural tradition through the longterm project-an immanent critique of German idealist and romantic aesthetics-which unites his writings. McCole builds a sustained reading of Benjamin's intellectual development which sheds new light on the formative role of early influences--particularly his participation in the pre-World War I German youth movement and the orthodox discourse of German intellectual culture--and shows how Benjamin later extended the strategies he learned within these contexts during key encounters with Weimar modernism, surrealism, and the fiction of Proust.The fullest account of Benjamin available in English, this lucid and penetrating book will be welcomed by intellectual historians, literary theorists and critics, historians of German literature, and Continental philosophers.